Pengaruh Motivasi Terhadap Kinerja Karyawan Untuk Menghadapi Persaingan Di PT Telkom Jawa Barat - Cuk Jaka Purwanggono (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
The research is purposed to know how motivational factors consisting of salary and social security, career expectation, managerial role, employee competence, work type, job equipment, work environment, and company policy—influence employee performance at a telecommunication company in West Java. The research is a survey one to generate scientific information using explanatory research. Data of the research is analyzed with a simple regression analysis and multiple regression analysis. Besides, the research experiences t-test, F-test, correlation coefficient, and determination coefficient calculated with an SPSS Version 12 program. Results of the research indicate that motivational factors have, both individually and collectively, significant influences on employee performance, with employee competence being the most dominant factor influencing employee performance at a telecommunication company in West Java. Keywords       : Motivation, performance, competition